2022
DOI: 10.1371/journal.pone.0269491
|View full text |Cite|
|
Sign up to set email alerts
|

Cingulate transcranial direct current stimulation in adults with HIV

Abstract: Background Neuronal dysfunction plays an important role in the high prevalence of HIV-associated neurocognitive disorders (HAND) in people with HIV (PWH). Transcranial direct current stimulation (tDCS)—with its capability to improve neuronal function—may have the potential to serve as an alternative therapeutic approach for HAND. Brain imaging and neurobehavioral studies provide converging evidence that injury to the anterior cingulate cortex (ACC) is highly prevalent and contributes to HAND in PWH, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 74 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…In the other studies, a monopolar montage was utilized, where one electrode was placed on the scalp, and the other was positioned extracerebrally, such as on the arm. The studies [43][44][45][46][47][48] found were published between 2012 and 2022. Among the included studies, three adopted parallel designs, and one adopted a crossover design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the other studies, a monopolar montage was utilized, where one electrode was placed on the scalp, and the other was positioned extracerebrally, such as on the arm. The studies [43][44][45][46][47][48] found were published between 2012 and 2022. Among the included studies, three adopted parallel designs, and one adopted a crossover design.…”
Section: Resultsmentioning
confidence: 99%
“…The studies [ 43 , 44 , 45 , 46 , 47 , 48 ] found were published between 2012 and 2022. Among the included studies, three adopted parallel designs, and one adopted a crossover design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that tDCS has excellent potential to enhance cognitive and motor impairments in those living with H.I.V. A study conducted by Jiang et al, (2022) revealed that participants with H.I.V. who underwent tDCS demonstrated enhanced preservation errors in the Wisconsin card sorting test, a measure of executive functioning, as well as improved scores in the ratio score of the trail making test, which assesses cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%